Social and cultural change in Poland and the revival of universally accessible sport - Dziubiński, Zbigniew (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
This paper aims to highlight the reasons behind the revival of universally accessible sport among the Polish public from the perspective of the social and cultural change that has taken place in Poland. The goal is to substantiate this revival through social sciences and theories of social change that dominate such sciences. The analysis below identifies two groups of key factors that have stimulated the public’s participation in universally accessible sport. The first group are social factors such as a surge in the number of people with higher education, the statistically increased affluence of Polish people, a higher percentage of white-collar workers, migration from rural to urban areas, and improved access to sports equipment and facilities. Factors in the other group are of cultural nature and include the following: the prevalence of aesthetic and hedonistic models of physical culture in society, the increased prestige and significance of sport consumption in the public’s consumption of culture, and the activation of informal social control in society, leading to positive sanctions for engaging in sporting activity and negative sanctions for refusing to do so. This group of factors also includes a growing number of people who, guided by rational and empirical truths, cease to interpret the success of others through the categories of theological or biological determinism and instead, they opt to act individually and together with others, also when it comes to health and fitness. Finally, a growing percentage of people accept the truth that good health primarily depends on prevention and lifestyle rather than hospital treatment and medication.